The role of gut microbiota in insulin resistance: recent progress - Ji, Hongfang; Su, Shenglin; Chen, Min; Liu, Shuhong; Liu, Shu; Guo, Jianjin (Frontiers in Microbiology, 2025)
Insulin resistance (IR) is the most critical pathophysiological basis of type 2 diabetes mellitus (T2DM). The mechanisms underlying IR are extremely complex, with variations observed among different patients and different tissues. Current research has gradually revealed characteristics of the gut microbiota and its role in metabolizing major nutrients during IR. The interaction between microbial communities and host metabolism has become a hotspot in modern medical research. This review aims to provide a comprehensive understanding of microbial metabolism related to IR by elucidating the effects of microbiota-carbohydrate metabolism and microbiota-host interactions on IR. Such insights may contribute to improving IR and offer novel perspectives for its treatment.